Influence of SIGLEC9 polymorphisms on COPD phenotypes including exacerbation frequency. Issue 4 (22nd November 2016) - Ishii, Takeo; Angata, Takashi; Wan, Emily S.; Cho, Michael H.; Motegi, Takashi; Gao, Congxiao; Ohtsubo, Kazuaki; Kitazume, Shinobu; Gemma, Akihiko; ParÉ, Peter D.; Lomas, David A.; Silverman, Edwin K.; et al.
ABSTRACT: Background and objective: The exacerbation‐prone phenotype of COPD is particularly important, as exacerbations lead to poor quality of life and disease progression. We previously found that COPD patients who lack Siglec‐14, a myeloid cell protein that recognizes bacteria and triggers inflammatory responses, are less prone to exacerbation. We hypothesized that the variations in other SIGLEC genes could also influence COPD exacerbation frequency, and investigated the association between SIGLEC9 polymorphisms and the exacerbation‐prone phenotype of COPD. Methods: We examined whether SIGLEC9 polymorphisms affect the frequency of COPD exacerbation in 135 subjects within our study population, and also analysed the correlation between the genotypes and the severity of airflow obstruction and emphysema in 362 Japanese smokers including 244 COPD patients. The association between these single nucleotide polymorphisms (SNPs) and COPD phenotypes were also assessed in a Caucasian population of ECLIPSE study. The effects of these coding SNPs (cSNPs) on Siglec‐9 protein functions were analysed using in vitro assays. Results: The G allele of rs2075803 and rs2075803 G/rs2258983 A(GA) haplotype in SIGLEC9 was associated with higher frequency of exacerbations and the extent of emphysema in COPD. These results did not replicate in the ECLIPSE study. A myeloid cell line expressing the Siglec‐9 variant corresponding to GA haplotype produced more TNF‐α than the one expressing the variant corresponding to the other major haplotype. Conclusion: The SIGLEC9 rs2075803 G/rs2258983 A haplotype, which corresponds to a Siglec‐9 variant that is less effective at suppressing inflammatory response, may be a risk factor for the development of emphysema. Abstract : A haplotype of SIGLEC9 gene was associated with exacerbation frequency and emphysema in Japanese COPD patients (but not in ECLIPSE cohort). The Siglec‐9 protein encoded by this haplotype was hypomorphic in its ability to suppress myeloid cell inflammatory responses. This study reinforces the connections between endogenous lectins and COPD phenotypes.